Effect of air temperature on growth performance, apparent digestibilities, rumen fermentation and serum metabolites in Altay and Hu lambs. Issue 4 (3rd February 2020) - Zhou, Jianwei; Ji, Kaixi; Liu, Hu; Zhang, Yunsheng; Degen, Abraham Allan; Jiao, Dan; Wang, Wenqiang; Xie, Zhongkui; Wang, Xinhua; Zhou, Ping; Yang, Guo
Abstract: Fat‐tailed Altay sheep are indigenous to the Altay prefecture and well adapted to severe cold and sparse pasture of poor quality. Hu sheep were introduced to this region in the 1970s and are raised mainly in feedlots. We hypothesized that the dietary energy utilization would differ between breeds and predicted that Altay sheep would be more efficient than Hu sheep, in particular at a low air temperature. To test this prediction, we examined growth performance, apparent digestibilities, rumen fermentation and serum metabolites in Altay (32 ± 2.6 kg) and Hu sheep (31 ± 2.7 kg) at air temperatures of −5 and 20°C. Average daily gain (ADG), feed and metabolizable energy intakes were greater in Altay than in Hu sheep ( p  < .01), and all were greater at −5°C than 20°C ( p  < .01). Body mass gain‐to‐feed intake ratio was higher in Altay than in Hu sheep ( p  < .001), but was not affected by air temperature ( p  > .10). Rumen total volatile fatty acid (VFA) concentration was greater in Hu than in Altay sheep ( p  < .05) and was greater at 20°C than at −5°C ( p  < .05), while rumen microbial protein concentration was greater in Altay than in Hu sheep ( p  < .05). Rectal temperature was higher at −5°C than 20°C ( p  < .05) and was similar between breeds ( p  > .05). Serum glucose, non‐esterified fatty acid (NEFA) and urea‐N concentrations were higher in Hu than in Altay sheep ( p  < .05). It was concluded that Altay sheep are better able to cope with poor quality diets as they had higher digestibility of nutrients, ADG and body mass gain‐to‐feed intake ratio than Hu sheep.